Oil price shocks, economic policy uncertainty, and green finance: a case of China - Wang, Kai-Hua; Su, Chi-Wei; Umar, Muhammad; Lobonţ, Oana-Ramona (Technological and Economic Development of Economy, 2023)
This study investigates the long- and short-run effects of crude oil price (COP) and economic policy uncertainty (EPU) on China’s green bond index (GBI) using the quantile autoregressive distributed lag model. The empirical results show that COP and EPU produce a significant positive and negative influence on GBI in the long-run across most quantiles, respectively, but their short-run counterparts are opposite direction and only significant in higher quantiles. Thus, major contributions are made accordingly and shown in the following aspects. The findings emphasise the importance of understanding how COP and EPU affect China’s green bond market for the first time. In addition, both the long- and short-run effects are captured, but long-run shocks primarily drive the green bond market. Finally, time- and quantile-varying analyses are adopted to explain the nexus between COP and EPU to GBI, which considers not only different states of the bond market but also events that occur in different time periods. Some detailed policies, such as a unified and effective green bond market, an early warning mechanism of oil price fluctuation, and prudent economic policy adjustments, are beneficial for stabilising the green finance market. First published online 19 December 2022